PENERAPAN PMRI MENGGUNAKAN POWERPOINT DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP MUHAMMADIYAH 6 PADANG - Warman, Joni; Rahmi, Rahmi; Cessaria, Anna (Pendidikan Matematika, 2013)
The research is based by the low of comprehension of studentsâ Â mathematical concept and students are less given opportunity to construct their own mathematical ideas, resulting of low yields students learn math. One way to solve this problem is to apply the approach of Indonesian Realistic Mathematics Education (I-RME) using PowerPoint. The research aims to determine whether the students comprehension of mathematical concept by applying I-RME using PowerPoint better than students comprehension of mathematical concept that apply conventional learning. PowerPoint is used as a medium of learning and facilitate the display context that is used to make students more focused on activities reinvent mathematical concept being studied. Type of research is experimental research, the entire population of 8th grade students of Junior High School Muhammadiyah 6 Padang and the sampling technique is random. The instrument used was the final test with indicator comprehension of mathematical concept. Form of test was used essay in the reliability of the test is 0.86. Data were analyzed by t-test using MINITAB obtained P-value =0.027 is less than Î±=0.05. It can be concluded that the students comprehension of mathematical concept by apply I-RME Â using PowerPoint better than students comprehension of mathematical concept that apply conventional learning.